Climate change from B to Z: a cross-generational perception study in Spain - Divasson-J, Asier; Aguayo-Mendoza, Armando; Quesada, Carlos; Casado-Mansilla, Diego; Borges, Cruz E. (Frontiers in Environmental Science, 2025)
In the context of increasing climate concerns, this study explores generational perceptions and responses to potential climate-induced crises through a workshop and survey methodology. The aim of this study is to understand how different age groups view and react to extreme climate scenarios and evaluate their proposed actions and attitudes toward climate change mitigation. This study investigates generational perceptions and responses to climate change through a dual-format workshop and survey, conducted both in person and online. The methodological approach involved presenting respondents with a range of apocalyptic scenarios resulting from climate change, including electricity shortages, reduced food production, fuel scarcity, inadequate home heating, drought, and raw material shortages. These scenarios aimed to assess respondents’ awareness, concern, and proposed actions in response to potential future crises. The survey, administered via the Prolific platform, and workshops, held at the “Zientzia Azoka” science fair and online, gathered data from 153 participants across four generational cohorts, namely, Baby Boomers, Generation X (Gen X), Millennials, and Generation Z (Gen Z). The analysis revealed distinct generational differences in attitudes toward societal responsibility and action. Baby Boomers emphasized community responsibility over formal regulations, showing a preference for moral and ethical accountability rather than legislative action. Generation X displayed balanced responses, with tendencies toward valuing education and long-term stability. Millennials were more likely to emphasize the role of authorities and formal governance in addressing societal issues, reflecting their reliance on structured systems. In contrast, Generation Z showed a strong inclination to hold companies accountable, often associating responsibility with corporate entities, and were more vocal about behavioral changes and restrictions to drive progress. The study underscores significant generational differences in climate change perceptions and actions, highlighting a trend toward increasing demand for climate action and growing distrust in institutions. These insights suggest the need for inclusive, generationally tailored climate policies with a focus on education and systemic change. Future research should explore the relationship between sustainable consumption and economic vulnerability, addressing how financial constraints impact individuals’ ability to adopt sustainable practices.